The human meaning of religion : an enquiry into the possibility of the translation of Christian faith into secular language with special reference to Kant and Hegel - Shutte, M. F. N.(Michael Frederick Neale) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.) -- Stellenbosch Universiteit, 1971.